BALANCING INTELLECTUAL PROPERTY PROTECTION AND RELEASE OF EXCLUSIVE RIGHTS FOR SUSTAINABILITY PURPOSES - Prisandani, Ulya Yasmine (JIPRO: Journal of Intellectual Property, 2024)
This paper explores the balance between intellectual property protection and its release for sustainability purposes within the Indonesian legal framework. While intellectual property rights incentivize innovation by granting creators exclusivity, they can also hinder the accessibility of technologies essential for achieving sustainability goals, particularly in resource-constrained regions. The study mentions global examples, including open-source initiatives by Tesla and Toyota, and examines their implications for fostering innovation and promoting equitable access to sustainable technologies. Drawing from Indonesian laws on intellectual property and international frameworks, the paper investigates the extent to which Indonesia's legal regime accommodates intellectual property release mechanisms like compulsory licensing, patent pools, and creative commons. Using a normative legal research method, this study identifies the gaps and opportunities in Indonesia's intellectual property regime. It emphasizes the critical role of stakeholders such as corporations, the government, and international organizations in matching intellectual property protection strategies with sustainability objectives. Companies as intellectual property owners are urged to adopt sustainability-oriented approaches that integrate intellectual property release while safeguarding their commercial interests. Governments are encouraged to implement supportive policies, including incentives and regulations, to promote technology sharing. Furthermore, global entities like WIPO are called upon to foster international frameworks that prioritize sustainable development. Ultimately, this paper advocates for a collaborative, multi-stakeholder approach to ensure intellectual property systems advance innovation while addressing urgent environmental and social challenges.